Efficacy and Safety of Immunotherapies in Refractory Myasthenia Gravis: A Systematic Review and Meta-Analysis - Feng, Xuelin; Song, Zubiao; Wu, Mengli; Liu, Yanmei; Luo, Sushan; Zhao, Chongbo; Zhang, Weixi (Frontiers in Neurology, 2021)
Introduction: Approximately 10–20% of patients WITH myasthenia gravis (MG) are refractory to conventional immunotherapies. The purpose of this study was to conduct a systematic review and meta-analysis to explore the optimal therapies for refractory MG. Method: Correlative studies were performed through a search in PubMed, Cochrane Library, and Embase databases. The primary outcome was defined by changes in the quantitative myasthenia gravis score (QMG). Secondary outcomes were defined by the Myasthenia Gravis Activities of Daily Living Scale (MG-ADL), Myasthenia Gravis Foundation of America (MGFA) post intervention status, adverse events, and disease exacerbation after treatment. Result: A total of 16 studies were included with 403 patients with refractory MG on therapies with rituximab, eculizumab, tacrolimus, and cladribine. Therapeutic efficacy of rituximab and eculizumab was identified with an estimated reduction in QMG score (4.158 vs. 6.928) and MG-ADL (4.400 vs. 4.344), respectively. No significant changes were revealed in efficacy or exacerbation density between the two independent therapeutic cohorts. The estimated adverse event density of eculizumab was more significant than that in the rituximab group (1.195 vs. 0.134 per patient-year), while the estimated serious event density was similar. Conclusion: The efficacy and safety of rituximab and eculizumab have been approved in patients with refractory MG. Rituximab had a superior safety profile than eculizumab with a lower incidence of adverse events. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021236818, identifier CRD42021236818.